2018
DOI: 10.1016/j.bbagen.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β modulates pancreatic cancer associated fibroblasts cell shape, stiffness and invasion

Abstract: Our findings elucidate on the effects of TGF-β on CAFs' behavior and stiffness providing new insights into the mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 74 publications
(114 reference statements)
7
51
0
Order By: Relevance
“…The cell cytoskeleton consists of three types of filaments (including actin microfilaments, intermediate filaments and microtubules) with actin filaments being considered the most significant for modulating the mechanical properties of cells [26]. Our results demonstrated that both CAFs and FBs exhibited intense stress fibres (which refers to a qualitative measure of how strong stress fibres are stained with phalloidin), while CAFs also exhibited increased formation of lamellipodia, the sheet-like membrane protrusions involved in cell movement, suggesting that CAFs have a more migratory phenotype (electronic supplementary material, figure S3B), in agreement with previous studies [27]. As tumour stiffening is an important consequence of desmoplasia, we investigated the effect of matrix stiffness on basic cellular characteristics of pancreatic FBs and CAFs, such as cell stiffness, a-SMA expression (the most common FB activation marker), cell spreading and stress fibre formation and orientation.…”
Section: Matrix Stiffening Increases Young's Modulus Of Fibroblasts Asupporting
confidence: 91%
See 2 more Smart Citations
“…The cell cytoskeleton consists of three types of filaments (including actin microfilaments, intermediate filaments and microtubules) with actin filaments being considered the most significant for modulating the mechanical properties of cells [26]. Our results demonstrated that both CAFs and FBs exhibited intense stress fibres (which refers to a qualitative measure of how strong stress fibres are stained with phalloidin), while CAFs also exhibited increased formation of lamellipodia, the sheet-like membrane protrusions involved in cell movement, suggesting that CAFs have a more migratory phenotype (electronic supplementary material, figure S3B), in agreement with previous studies [27]. As tumour stiffening is an important consequence of desmoplasia, we investigated the effect of matrix stiffness on basic cellular characteristics of pancreatic FBs and CAFs, such as cell stiffness, a-SMA expression (the most common FB activation marker), cell spreading and stress fibre formation and orientation.…”
Section: Matrix Stiffening Increases Young's Modulus Of Fibroblasts Asupporting
confidence: 91%
“…Indeed, when cultured on rigid substrates, CAFs proved to be softer than FBs, forming monolayers with oriented cellular patterns ( figure 1). AFM studies have demonstrated that cancer cells, which are highly invasive, are also softer than normal cells [32,33], while they also remodel their cytoskeleton so as to facilitate their invasion through surrounding stiff tissues [27,53]. Similarly, we showed here that while CAFs are softer than FBs in stiff substrates and possess a more invasive phenotype reminiscent of that of cancer cells, both cell lines become stiffer in stiffer environments [54,55] when they encounter higher levels of stress.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is expected though that the mechanical properties of the cell cortex in a spread and a suspended state vary, as the cortical thickness depends on cell spreading and is altered on de-adhesion of cells [ 72 ]. Recently, pancreatic CAFs were reported to exhibit a lowered elastic modulus compared with native fibroblasts from the pancreas, although similar changes in the stress fiber alignment as in our study were observed [ 73 , 74 ]. There are, however, some differences in the experimental setup.…”
Section: Discussionsupporting
confidence: 86%
“…Briefly, before each experiment, the cells were washed twice with PBS and new complete media was added. The petri dish (35 mm) was mounted directly on the AFM specimen disc and all the experiments were performed under liquid condition (cells' complete media) at room temperature [10,41,42]. AFM experiments: A Molecular Imaging-Agilent PicoPlus AFM system (now known as AFM 5500 Keysight technologies) with a round (2.5 μm radius) ball-shape tip (CP-PNPL-BSG), and spring constant of 0.08 N m −1…”
Section: Discussionmentioning
confidence: 99%